'In the vertigo of this freedom': Democracy between procedural and divided popular sovereignty. (November 2021) - Bozzon, Matteo
The aim of this article is to investigate the Habermasian way of problematizing the European political situation through consideration of the conceptual framework within which he develops his proposal. I begin by clarifying various conceptual difficulties that emerge when thinking about politics within the European Union. I then focus on the concept of popular sovereignty as procedure, which Habermas develops in Between Facts and Norms against the historical backdrop of the nation state. In the debate regarding European constitutionalization, the concept of popular sovereignty as procedure first assumes a critical function (made possible owing to its desubstantializing effect) against proponents of the no demos thesis. More recently, Habermas has advanced a concept of shared/divided sovereignty, which becomes indispensable when we consider Europe as a democratic federation. The conclusions hereby drawn disclose two problematic aspects of Habermas's recent proposal. Respectively, these concern the viability of his approach and the questionable plausibility of this proposed federation's ability to uphold democracy in terms of self-determination.